Designing for atmosphere: A level design approach to architecture - Sörensen, Axel (My University, 2025)
The limits of the real world have long been a challenge to architecture, to rein in the creativity of the mind to the constraints of the world. What then, would architects design if rules and regulations were no longer a constraint, and even gravity was optional? As such it comes to no surprise that some architects have migrated into the virtual world of level design. As these architects leave designing in the real world behind, their new creations are no longer seen as architecture, they are for video games, even though they too are a deep exploration of form, space, and atmosphere, and arguably with a stronger emotional connection to its world than the connection real-world architecture has to its own. But like all creative works, the value of architecture comes from taking a dream or feeling and finding a way to realise it. To shape the world for the beholder to have the best possible experience. Just like level designers. This thesis sought to nurture the connection between level design and architecture through design. To learn from the freedom of level design and capture its playful and fantastical essence and incorporate it into a project meant for the real world. Through literature and case studies a set of level design principles were established. These were adapted to work in the real world to then be applied to as a mixed-use project in central Gothenburg. The design-phase was divided into three key stages: Layout, establishing the goals and constraints, such as urban context and regulations; Block-out, focusing on spatial relationships, movement, and the exploration of the space; and Environment Art, refining the design to enhance materiality and detail, ensuring it connects to the surrounding city while maintaining its own identity. Throughout the phases, the design was analysed according to its atmosphere and realism through play-testing. Evaluating the effectiveness of the design compared to its realistic buildability and usage according to the dimensions of the spaces. Through this methodology, the final design emerged as a public path along the mixed use building, forming intricate spaces with a focus on atmosphere.
Keywords: Architecture, atmosphere, ad hoc design, method development, level design; adaptation, play-test, unreal engine